PENGARUH FLASH SALE TERHADAP MINAT BELI SOMETHINC DIMODERASI OLEH MOTIVASI BELANJA HEDONIS PADA PLATFORM TIKTOK SHOP - Siregar, Norberta; Triadinda, Dexi; Retnosary, Rieke (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyse how Somethinc’s flash sale programme on TikTok Shop influences purchase intent among Generation Z, with hedonistic shopping motivation serving as a moderating variable. The researcher employed a quantitative approach and collected data via a survey of TikTok Shop users who had previously used the Somethinc flash sale feature. The results of the analysis indicate that the flash sale has a positive and significant impact on hedonistic shopping motivation, and influences purchasing intention both directly and indirectly. Hedonistic shopping motivation was found to have a positive and significant effect on purchase intention, thereby acting as a key channel through which the flash sale influences consumers’ purchasing decisions. The coefficient of determination indicates that the research model possesses a moderate to strong explanatory power